Effects and moderators of psychosocial interventions on quality of life, and emotional and social function in patients with cancer: An individual patient data meta‐analysis of 22 RCTs. Issue 4 (15th March 2018) - Kalter, J.; Verdonck‐de Leeuw, I.M.; Sweegers, M.G.; Aaronson, N.K.; Jacobsen, P.B.; Newton, R.U.; Courneya, K.S.; Aitken, J.F.; Armes, J.; Arving, C.; Boersma, L.J.; Braamse, A.M.J.; et al.
Abstract: Objective: This individual patient data (IPD) meta‐analysis aimed to evaluate the effects of psychosocial interventions (PSI) on quality of life (QoL), emotional function (EF), and social function (SF) in patients with cancer, and to study moderator effects of demographic, clinical, personal, and intervention‐related characteristics. Methods: Relevant studies were identified via literature searches in 4 databases. We pooled IPD from 22 ( n  = 4217) of 61 eligible randomized controlled trials. Linear mixed‐effect model analyses were used to study intervention effects on the post‐intervention values of QoL, EF, and SF (z‐scores), adjusting for baseline values, age, and cancer type. We studied moderator effects by testing interactions with the intervention for demographic, clinical, personal, and intervention‐related characteristics, and conducted subsequent stratified analyses for significant moderator variables.Results: PSI significantly improved QoL (β = 0.14, 95%CI = 0.06;0.21), EF (β = 0.13, 95%CI = 0.05;0.20), and SF (β = 0.10, 95%CI = 0.03;0.18). Significant differences in effects of different types of PSI were found, with largest effects of psychotherapy. The effects of coping skills training were moderated by age, treatment type, and targeted interventions. Effects of psychotherapy on EF may be moderated by cancer type, but these analyses were based on 2 randomized controlled trials with small sample sizes of some cancer types. Conclusions: PSI significantly improved QoL, EF, and SF, with small overall effects. However, the effects differed by several demographic, clinical, personal, and intervention‐related characteristics. Our study highlights the beneficial effects of coping skills training in patients treated with chemotherapy, the importance of targeted interventions, and the need of developing interventions tailored to the specific needs of elderly patients.